The use of geogebra interactive multimedia on spatial ability of elementary students in 2020-2024 period - Siti Aminah; Fathur Rokhman; Suwito Eko Pramono; Bambang Subali; Nuni Widiarti (Jurnal Ilmiah Pendidikan Dasar, 2025)
Spatial ability constitutes a critical cognitive skill that facilitates students' capacity to comprehend and manipulate spatial information. In recent years, the integration of technology—particularly interactive multimedia tools such as GeoGebra—has garnered increasing attention as a means to enhance spatial ability among elementary school students. This study presents a literature review examining the effectiveness of GeoGebra in fostering spatial abilities in elementary education between 2020 and 2024. A total of eleven peer-reviewed articles were identified using Harzing’s Publish or Perish software in conjunction with Google Scholar. Each study was systematically analyzed, and pertinent data were synthesized into a table summarizing the title, authorship, year of publication, and principal findings. The review indicates that, relative to conventional instructional methods, the use of GeoGebra significantly enhances students’ mathematical comprehension. Key trends identified include notable improvements in visualization, mental rotation, and spatial problem-solving abilities among students engaged in GeoGebra-based instruction. The findings underscore the potential of GeoGebra as an effective pedagogical tool for promoting spatial reasoning and conceptual understanding in elementary mathematics education. These insights carry important implications for curriculum development, suggesting that technology-enhanced learning environments can foster greater student engagement and a deeper grasp of geometric concepts.